Penerapan Strategi Reading Aloud dengan Model Kontekstul untuk Menumbuhkan Minat Membaca Siswa Kelas V Sekolah Dasar Inpres Nusa Tenggara Timur - Ahmad Wiranto; Abdul Wahid; Rahmawati, Rahmawati (Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Makassar, 2024)
Abstract: This study aims to determine the improvement of students' reading interest ability through the application of reading aloud strategies with contextual models in class V Inpres Elementary School, East Nusa Tenggara. This research is classroom action research, which was conducted in two cycles and each cycle. The subjects of this study were 1 teacher and 20 students of class V of Inpres Elementary School, East Nusa Tenggara. Data collection techniques using observation techniques, tests, and documentation. The results showed that reading ability only reached 60.5 and was in the sufficient category. Then after applying the reading aloud strategy in cycle I the average student reading ability increased to 70 and was in the good category. In Cycle II, the average reading ability of students increased further, reaching 80.5 or in the excellent category. It can be concluded that the reading aloud strategy with a contextual model can foster the interest in reading of grade V students at Inpres Elementary School, East Nusa Tenggara.